2013
DOI: 10.1590/s1413-81232013000100005
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade do atendimento nas Unidades de Saúde da Família no município de Recife: a percepção do usuários

Abstract: Qualidade do atendimento nas Unidades de Saúde da Família no município de Recife: a percepção do usuáriosQuality of care in the family healthcare units in the city of Recife: user perception

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
28
0
49

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 10 publications
5
28
0
49
Order By: Relevance
“…Short waiting time can be a factor that contributed to the high scores in quality of speech therapy services, as other research indicates generally long waiting times for examinations and/ or queries related to audiological health services (13,20,21) . P34's statement shows that SUS services are not thought of as being fast or efficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short waiting time can be a factor that contributed to the high scores in quality of speech therapy services, as other research indicates generally long waiting times for examinations and/ or queries related to audiological health services (13,20,21) . P34's statement shows that SUS services are not thought of as being fast or efficient.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the literature indicates that there is a differential related to purely public SUS services and those carried out in private-public partnerships (21,22) . The waiting for appointments at some public centers for consults/ exams can reach years, while for private partner centers, such as the center in this study, the wait is less, reaching up to around a six-month wait.…”
Section: Discussionmentioning
confidence: 99%
“…The shortcomings in the Brazilian scientific publications on the exclusive or predominant perspective of the male population on PHC are highlighted. On the one hand, the lower demand of men in the FHT may be due to a greater link with work; on the other, because the PHC service does not prioritize these users (15) . In this sense, a study with men in Minas Gerais, Brazil, found participants in the 51-59 age group (37.3%), followed by 41 to 50 years (27.6%) (16) .…”
Section: Discussionmentioning
confidence: 99%
“…Ainda, o perfil dos usuários entrevistados foi predominantemente feminino, o que também foi verificado em outros estudos envolvendo usuários do serviço público de saúde 6,19,21,29,32 . Para Santiago et al 32 (2013), o alto número de mulheres demonstra a importância delas como usuárias do serviço público e como cuidadoras da saúde de sua família.…”
Section: Discussionunclassified
“…Para Santiago et al 32 (2013), o alto número de mulheres demonstra a importância delas como usuárias do serviço público e como cuidadoras da saúde de sua família. A menor participação dos homens pode ser decorrente de um maior vínculo com o trabalho, buscando alternativas para a assistência, e também pela não priorização desses usuários nas unidades de saúde 19,32 .…”
Section: Discussionunclassified